Removal of posts from root canals using ultrasounds* - Olczak, Katarzyna; Pawlicka, Halina (Journal of Stomatology, 2017)
Introduction. The removal of crown-root inlays and subsequent root canal re-treatment require from the dentist experience and skills to use modern instruments. Before treatment we should carefully examine the situation in the mouth and consider all the factors associated with the prognosis of planned procedures. Currently, the energy of ultrasound waves is often recommended and used to remove crown-root inlays. Aim of the study. To present the possibilities of the crown-root inlays removal using ultrasounds. Material and methods. The described clinical cases involve root canal re-treatment and the removal of crown-root inlays. Conclusion. The removal of crownroot inlays is not a simple procedure. The use of modern equipment, such as a microscope and ultrasonic scaler can contribute to the therapeutic success. The choice of management depends on the clinical situation and the doctor’s decision.